Exploring the Application of Bifunctional Metal Chelators in Treating Triple-Negative Breast Cancer - Li, Kuo; Zhang, Youjiu; Wang, Xiaomei; Zhu, Ran; Ma, Changsheng; Hu, Rui (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: In this study, we independently synthesised and labelled a novel bidentate bifunctional chelating agent, 177Lu-3,4-HOPO-Cetuximab, that achieved tight binding between targeting and radioactivity, and evaluated its targeted killing ability of cells in vitro and in vivo. Method: 3,4-HOPO was successfully synthesised through a series of chemical steps using malt phenol as the raw material, which was then coupled with Cetuximab labelled with 177Lu. 177Lu-3,4-HOPO-Cetuximab and 177Lu-DOTA-Cetuximab was tested for its cell viability and cell-binding rate after different times and at different doses by CCK-8 and cell-binding experiments. 177Lu-3,4-HOPO-Cetuximab (~500 μCi) and 177Lu-DOTA-Cetuximab (~500 μCi) were injected into the tail vein of a subcutaneous metastasis mouse model of triple-negative breast cancer with a single injection, and tumour volume growth and body weight changes were regularly monitored for 20 days. The radioactivity distribution in nude mice was analysed after sacrifice, and the treated and untreated tumour tissues were analysed by HE staining. Result: The cell viability of 177Lu-3,4-HOPO-Cetuximab declined exponentially after treatment for 48 h at 50 Bq/mL to 500 kBq/mL, respectively; the cell activity was slowed down from 8 to 96 h at a dose of 500 kBq; while the binding rate of 4T1 cells in 177Lu-3,4-HOPO-Cetuximab from 1 to 24 h, respectively, increased logarithmically, which was similar with 177Lu-DOTA-Cetuximab. After 20 days of treatment, the body weight of nude mice with 177Lu-3,4-HOPO-Cetuximab and 177Lu-DOTA-Cetuximab were hardly changed, while the body weight with physiological saline decreased significantly. The tumour inhibition rate of the 177Lu-3,4-HOPO-Cetuximab and 177Lu-DOTA-Cetuximab were (37.03 ± 11.16)% and (38.7 ± 5.1)%; HE staining showed that tumour cells were affected by the action of 177Lu causing necrosis. Conclusion: The experiments showed that 177Lu-3,4-HOPO-Cetuximab has a certain targeted therapeutic ability for triple-negative breast cancer, and it is expected to become a potential targeted nuclear medicine treatment for triple-negative breast cancer.